Love and Life: An Old Story in Eighteenth Century Costume - Yonge, Charlotte M. (Charlotte Mary), 1823-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"Love and Life: An Old Story in Eighteenth Century Costume" by Charlotte M. Yonge is a historical novel set in the early 19th century. The narrative revolves around the enchanting tale of Psyche and Cupid, reimagined within the context of 18th-century English society. The central focus seems to be on the lives of the Delavie sisters, particularly Aurelia, as they navigate love, societal pressures, and familial duties amidst a backdrop of traditions and expectations. The opening of the novel introduces Major Delavie, a retired officer, as he awaits the return of his daughters from a festive outing. Through a detailed description of their home and lifestyle, we encounter the characters of the sisters$1 (BAurelia, Harriet, and Betty$1 (Bas they discuss their experiences at a syllabub party. Aunt Betty, the eldest sister, takes on a maternal role, ensuring her siblings' well-being while grappling with her feelings about societal expectations and familial honor. Amidst playful banter and fatherly affection, hints of romantic intrigue and tension surface, particularly regarding the youngest sister Aurelia, foreshadowing her future entanglements and the larger themes of love and sacrifice woven into the tale. (This is an automatically generated summary.)s
Release date is 2004-05-01
Produced by Doug Levy, and David Widger
Keywords: English fiction -- 19th century